2008
DOI: 10.1016/j.sigpro.2007.08.011
|View full text |Cite
|
Sign up to set email alerts
|

On approximation of smooth functions from samples of partial derivatives with application to phase unwrapping

Abstract: This paper addresses the problem of approximating smooth bivariate functions from the samples of their partial derivatives. The approximation is carried out under the assumption that the subspace to which the functions to be recovered are supposed to belong, possesses an approximant in the form of a principal shift-invariant (PSI) subspace. Subsequently, the desired approximation is found as the element of the PSI subspace that fits the data the best in the 2 -sense. In order to alleviate the ill-posedness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In this case, the functionals (21) and (22) can be considered to be real-valued functions of a complex vector, whose first and second derivatives can be computed by the standard methods of calculus.…”
Section: B Numerical Optimization Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this case, the functionals (21) and (22) can be considered to be real-valued functions of a complex vector, whose first and second derivatives can be computed by the standard methods of calculus.…”
Section: B Numerical Optimization Methodsmentioning
confidence: 99%
“…By analogy, the same convex term can be added to the ML cost functional (12) resulting in (22) However, while in the case of (21), the addition of was done in order to improve the numerical characteristics of the resulting minimization, in the case of (22) this becomes a necessity. The fact is that, for the PSF used in the present study, without adding this term, it was found impossible to achieve stable convergence to the local minima of (12) for any value of parameter λ.…”
Section: A Regularization Revisedmentioning
confidence: 99%
See 3 more Smart Citations